A Fronteira Moçambique-Zimbabué e os ndau: Práticas e representações transfronteiriças no distrito moçambicano de Mossurize (de 1975 à actualidade) - Marta Patrício (Cadernos de Estudos Africanos)
Perspectives on African borders, in general, are often based on assertions that the borders are artificial and arbitrary. However, this type of categorization seems to reveal ignorance against the practices and meanings that people attach to the local borders. This article seeks to contribute to this literature through a case study in Mossurize district, on the border between Mozambique and Zimbabwe. Original empirical evidence seeks to demonstrate how ndau border groups perceive and relate to the border and with their kinsmen living “on the other side”, and how major changes in the economic policy of one of those states has repercussions throughout the porous border.